The effectiveness of Customer Management Department in Telekom Malaysia consumer sales Selangor in retaining their existing customers / Nur Solatul Ima Sahidan - Sahidan, Nur Solatul Ima (Faculty of Business and Management, 2008)
This study was an attempt to examine the effectiveness of Customer Management Department in Telekom Malaysia Consumer Sales Selangor in retaining their existing customers. The objectives of the study reported in this paper were to identify the satisfaction of customers towards TM Consumer Sales Selangor’s customer service as well as staff job satisfaction. Face to face personal interview had been done to get staffs’ comment towards their job satisfaction and telephone personal interview had been done to get customers’ comment about TM customer services. Finding on the customers’ satisfaction towards TM customer service shows that there are customers who can accept TM approach to get their personal details and cooperate and some are refused to cooperate for security reason. Findings on the staffs’ comment towards their job satisfaction, their motivation will reduce if customers refuse to cooperate and it caused to turn off their job interest as well. Based on the finding of customers’ performance after they were selected to TM loyalty program, the positive effectiveness of TM approach to award and increase customers’ loyalty towards TM services can be seen from the positive monthly bills paid. Findings of this study also generated some suggestions that can be applied to increase the level of satisfaction of TM customers as well as TM staffs.